The impact of COVID-19 on clinical course and treatment among patients with juvenile systemic sclerosis - Amra Adrovic,; Mehmet Yıldız,; Fatih Haşlak,; Sezgin Şahin,; Oya Köker,; Aybüke Günalp,; Kenan Barut,; Özgür Kasapçopur, (Archives of Rheumatology, 2023)
Objectives: This study aimed to explore the influence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic among patients with juvenile systemic sclerosis (JSS). Patients and methods: Twenty-seven patients (22 females, 5 males; mean age: 20 years; range, 17 to 22 years) diagnosed with JSS and followed up at the department of pediatric rheumatology were included in the cross-sectional study. A web-based survey was performed by focusing on patients’ complaints, accessibility to health care, and compliance with routine treatment from January 1, 2021, to January 10, 2021. Results: Five (18.5%) patients had deterioration of the disease, while six (22.2%) patients reported irregular usage of their routine scleroderma treatment during the last six months. Nine (33.3%) patients had missed their routine clinic control since the proclamation of the SARS-CoV-2 pandemic. Seven (25.9%) patients had household contact with coronavirus disease 2019 (COVID-19). Four (14.8%) patients were diagnosed with COVID-19, and only one (3.7%) was hospitalized. Nine patients were under biological treatment (tocilizumab); however, only one of them was diagnosed with COVID-19. Conclusion: The COVID-19 pandemic has not significantly disrupted the medical care of JSS patients. Telemedicine could be an acceptable option for JSS patients disenabled to come to the hospital.